All the pretty horses - McCarthy, Cormac, 1933- (New York : Vintage International, 1993)
The story of young John Grady Cole, the last of a long line of Texas ranchers, who, along with two companions, sets off on an idyllic, sometimes comic adventure, to a place where dreams are paid for in blood.
Originally published: New York : Alfred A. Knopf, 1992.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Wilson's Senior High School.
Adult
Keywords: Ranch life -- Texas -- Fiction; Adventure fiction; Bildungsromans; Ranch life -- Fiction; Texas -- Fiction; Texas -- Fiction; Adventure stories; Bildungsromane